Exercise Reduces Infarct Volume and Facilitates Neurobehavioral Recovery: Results From a Systematic Review and Meta-analysis of Exercise in Experimental Models of Focal Ischemia. (October 2014) - Egan, Kieren J.; Janssen, Heidi; Sena, Emily S.; Longley, Lesa; Speare, Sally; Howells, David W.; Spratt, Neil J.; Macleod, Malcolm R.; Mead, Gillian E.; Bernhardt, Julie
Background . Regular exercise reduces the risk of a first-ever stroke and is associated with smaller infarcts. Although evidence has suggested that therapeutic exercise following stroke is beneficial, we do not yet know whether exercise reduces stroke severity and improves functional recovery. The mechanisms underlying any benefit remain unclear. Objective . To conduct a systematic review and meta-analysis of studies testing exercise in animal models of ischemic stroke where outcomes were measured as infarct volume, neurobehavioral score, neurogenesis, or a combination of these. We also sought evidence of publication bias. Methods . We searched 3 online databases for publications reporting the use of exercise in focal cerebral ischemia. We used DerSimonian and Laird normalized random-effects meta-analysis and meta-regression to determine the impact of study quality and design on the efficacy of exercise. Results . Overall, exercise reduced infarct volume by 25.2% (95% confidence interval [CI] = 19.0%-31.3%; 65 experiments and 986 animals) and improved neurobehavioral score by 38.2% (95% CI = 29.1%-47.3%; 42 experiments; n = 771). For both outcomes, larger effects were seen when exercise preceded ischemia rather than came after it. For neurobehavioral scores, we found evidence of publication bias. Reported study quality was moderate (median score 5/10). Both model-specific (eg, type of ischemia) and exercise-specific characteristics influenced reported outcome. Conclusion . Exercise, either before or after ischemia, reduced infarct volume and improved neurobehavioral score. However, overall estimates of efficacy were higher in studies at risk of bias, and for neurobehavioral outcomes, there was evidence of a substantial publication bias.